Difficulties encountered by hearing impaired students, teachers and interpreters of the Brazilian Sign Language in teaching-learning human anatomy in higher education courses (Research, Society and Development, 2020)
The number of hearing impaired students that enter higher education courses has been continuously growing throughout Brazil. The present work surveyed the difficulties faced by deaf students in healthcare undergraduate courses, their teachers and the interpreters of the Brazilian Sign Language (LIBRAS) in the teaching-learning process of human anatomy. Data collection was carried out through interviews. The results showed that deaf students have great difficulty in learning anatomy in healthcare undergraduate courses. In all aspects, students, teachers and interpreters agreed that the greatest difficulty in the teaching-learning process of anatomy occurred due to the lack of specific signs for the anatomical terminology. The absence of these signs causes delays in the translation of the lesson and possible misinterpretation of the terms, due to distortions in dactilology, modifying the correct terminology, leading to conceptual errors and learning deficit.